2021
DOI: 10.1186/s13058-021-01415-w
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells and palbociclib treatment in patients with ER-positive, HER2-negative advanced breast cancer: results from a translational sub-study of the TREnd trial

Abstract: Background Circulating tumor cells (CTCs) are prognostic in patients with advanced breast cancer (ABC). However, no data exist about their use in patients treated with palbociclib. We analyzed the prognostic role of CTC counts in patients enrolled in the cTREnd study, a pre-planned translational sub-study of TREnd (NCT02549430), that randomized patients with ABC to palbociclib alone or palbociclib plus the endocrine therapy received in the prior line of treatment. Moreover, we evaluated RB1 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Besides, those patients with ≥5 CTC develop resistance earlier. RB expression was also analysed but there was no correlation with clinical benefit [55]. Although this is the first study reported based on CTCs enumeration or molecular analysis in these patients, a bigger cohort and more analysis are required, as CTC characterisation will increase their clinical utility.…”
Section: Circulating Tumour Cell (Ctc) Analysis As a Novel Biomarker For Managing Hr+/her2− Mbc Patientsmentioning
confidence: 97%
“…Besides, those patients with ≥5 CTC develop resistance earlier. RB expression was also analysed but there was no correlation with clinical benefit [55]. Although this is the first study reported based on CTCs enumeration or molecular analysis in these patients, a bigger cohort and more analysis are required, as CTC characterisation will increase their clinical utility.…”
Section: Circulating Tumour Cell (Ctc) Analysis As a Novel Biomarker For Managing Hr+/her2− Mbc Patientsmentioning
confidence: 97%
“…Additionally, molecular characterization of CTCs might increase their clinical validity [ 71 ]. The prognostic value of CTC was recently analyzed in patients enrolled in a translational sub-study of TREnd [ 30 ]. CTCs count after the first cycle of palbociclib (T1), but not at baseline was prognostic in terms of PFS.…”
Section: Additional Circulating Biomarkersmentioning
confidence: 99%
“…Indeed, patients with an increase of three or more CTCs at T1 experienced shorter PFS compared to those without increase. Intriguingly, patients whose CTCs showed detectable expression of RB1 at any time-point had better, although not statistically significant, outcomes compared to those with undetectable levels [ 30 ].…”
Section: Additional Circulating Biomarkersmentioning
confidence: 99%
“…Another important aspect concerns the opportunity to make serial withdrawals, allowing for the monitoring of the disease during treatment. Changes in CTC count proved to be clinically relevant [ 48 , 49 , 50 ]. In addition, longitudinal evaluation of CTC clusters proved to further improve prognostication as well as therapy monitoring in mBC patients starting first-line chemotherapy [ 51 ].…”
Section: Ctcs and Bcmentioning
confidence: 99%
“…As observed in patients diagnosed with ER-positive advanced BC and treated with Palbociclib in the cTREND study, CTC enumeration during treatment can be helpful to identify early-resistance to treatment. In addition, CTC count at progression can serve as a prognostic factor to predict post-palbociclib outcome but CTC enumeration at baseline did not show any significant prognostic value [ 48 ]. However, the raw CTC enumeration does not take into account the status of these cells.…”
Section: Ctcs and Bcmentioning
confidence: 99%